PREIMPLANTATION GENETIC TESTING - Jeremić, Ana; Vuković, Dragana; Subanović, Srna; Broćić, Jovana; Macanović, Biljana (Srpski medicinski časopis Lekarske komore, 2021)
INTRODUCTION: The application of preimplantation genetic testing (PGT) began in the late 1980s. Preimplantation genetic testing as the earliest possible way of prenatal diagnosis enables selection of embryos with a normal karyotype for embryotransfer. The use of preimplantation genetic testing has proven to be a useful method in three groups of inherited diseases: monogenic diseases, trinucleotide repeat disorders and chromosomal abnormalities. The success rate of in vitro fertilization (IVF) has increased significantly after PGT was introduced into clinical practice. AIM: Our paper presents a review of the literature with an aim of clearly determining the role of PGT in embryo selection before embryo transfer, as well as the role of this type of testing in increasing the success rate of IVF. One of the goals is to review the development of molecular genetic methods that are currently, or have been, in routine use when performing PGT. CONCLUSION: The current literature is an indicator of the development and progress of molecular genetics techniques applied in PGT. At the same time, it provides an opportunity and an incentive for further extensive research that will lead to the improvement of preimplantation genetic testing and thus increase the success rate of in vitro fertilization.